Knowledge of and willingness to perform Hands-Only cardiopulmonary resuscitation among college students in Malaysia - Karuthan, Sumitra Ropini; Firdaus, Putri Jasmine Filza; Angampun, Aloha Dee-Afryna George; Chai, Xuan Jia; Sagan, Chris Dom; Ramachandran, Monishak; Perumal, Sharmmathevan; Karuthan, Mahendra; Manikam, Rishya; Chinna, Karuthan (Lippincott, Williams & Wilkins, 2019)
Worldwide, millions of people die of sudden cardiac arrest every year. This is partly due to limited and sometimes ineffective bystander cardiopulmonary resuscitation (CPR). The need for mouth-to-mouth contact, fear of causing harm, litigation, and the complexity of delivering CPR are the main deterrents. In view of this, the basic life support algorithm has been simplified and lay rescuers are encouraged to perform Hands-Only CPR.The objective of this study is to assess knowledge on and willingness to perform Hands-Only CPR among Malaysian college students and to determine the relationship between the two.In an online self-administered survey, college students responded to a questionnaire on demographics, exposure to CPR, knowledge on Hands-Only CPR, and their willingness to perform Hands-Only CPR in 5 different scenarios (family members or relatives, strangers, trauma victims, children, and elderly people).Data for 393 participants were analyzed. For knowledge, the mean score was 8.6±3.2 and the median score was 9. In the sample, 27% of the respondents did not attend any CPR training before, citing that they were unsure where to attend the course. The knowledge score among those who attended CPR training (M=3.6, S=2.9) was significantly higher compared to those who did not (M=6.7, S=3.0). Out of the 393 participants, 67.7%, 55%, 37.4%, 45%, and 49.1% were willing to perform Hands-Only CPR on family members or relatives, strangers, trauma victims, children, and elderly people, respectively. There were significant associations (P<.001) between knowledge and willing to perform Hands-Only CPR on family members or relatives (OR=1.32, 95% CI 1.43, 1.43), strangers (OR=1.31, 95% CI 1.21, 1.42), trauma victims (OR=1.21, 95% CI 1.12, 1.31), children (OR=1.28, 95% CI 1.19, 1.39), and elderly people (OR=1.36 95% CI 1.25, 1.48).Based on this study, knowledge on Hands-Only CPR among local college students is not encouraging. Not many know where to attend such courses. There was significant association between knowledge and willingness to perform Hands-Only CPR. © 2019 the Author(s).